Implementasi Media Permainan Ular Tangga Terhadap Hasil Belajar IPA Pada Materi Siklus Air Kelas V SDN 31 Cakranegara - Fidhea Aisara; I Ketut Widiada; Muhammad Syazali (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to determine the effectiveness of the implementation of snakes and ladders game media on science learning outcomes in Class V water cycle material at SDN 31 Cakranegara. This type of research is experimental research using the Pre-Experimental design of the One Group Pretest-Posttest type. The research instrument used was a written test in the form of multiple choices. Before conducting an assessment of the hypothesis, a requirement test is carried out, namely the normality test. The normality test results obtained a significance value for the pretest data of 0.200 > 0.05 and a posttest significance value of 0.153 > 0.05 which means that the data is normally distributed. Once it is known that the data are normally distributed, a hypothesis test is carried out using the paired simple t-test with a value of 000 <0.05. This states that Ho is rejected and Ha is accepted, which means that there is a difference in learning outcomes between before and after being given the snakes and ladders media game treatment. science lesson about the water cycle for class V SDN 31 Cakranegara